Saudi oil policy: Continuity and change in the era of the energy transition - Bassam Fattouh (The Oxford Institute for Energy Studies, 2021)
The crucial position that Saudi Arabia has in global oil markets cannot be overstated. In 2019 its proven crude oil reserves stood at 297.6 billion barrels, representing 17 per cent of the world's total. In the same year Saudi Arabia produced 11.8 million barrels per day (mb/d) of crude, blended, and unblended condensates, and natural gas liquids. The country produces a wide array of crudes, ranging from Arab Super Light all the way to Arabian Heavy. Despite rising domestic demand in the past few decades, Saudi Arabia exports the bulk of its crude production and thus has a dominant position in international trade. It is the only country that has an official policy of maintaining spare capacity that can be utilized within a relatively short time at a low cost. Saudi Arabia's reserves are also among the cheapest in the world to find, develop, and produce. In contrast to some neighbouring countries and other OPEC members, such as Iran, Iraq, Libya, and Venezuela, Saudi Arabia has not experienced conflict or political instability and has not been subject to international sanctions. It has thus been able to invest heavily in its energy sector and integrate the upstream sector with refining and downstream assets, both in the kingdom and overseas. The oil and gas sectors are also heavily integrated, given the large volumes of associated gas produced. Saudi Arabia also has also a dominant position in OPEC and historically the organization's key decisions have been shaped by the kingdom, either those related to cutting output to balance the market or increasing output to offset output disruption within OPEC and elsewhere. Although Saudi Arabia's output has not been impacted by political or military shocks it has nonetheless been highly variable reflecting the kingdom's flexibility to increase and decrease output in response to shocks. Given its size and large margins, the oil sector also plays a key role in the Saudi economy. Despite new revenue sources, the government remains highly reliant on oil revenues for its current and capital spending. Also, government spending is a key driver of growth in non-oil and private-sector activity through infrastructure investment, public sector wage bills, and social transfers. All the aforementioned features, from the size of the kingdom's reserve base and production to the high reliance of government finances on oil revenues, have shaped Saudi oil policy choices and its relations with other producers over the years. The main purpose of this paper is to analyse a range of these policy choices and relations, their determinants, and the evolving role of the oil sector in the context of an energy transition, the speed of which remains highly uncertain and its impact uneven across the globe.
Keywords: 330; Adaptation Strategies; Diversification; Energy Transition; Oil Policy; OPEC; Saudi Arabia; Spare Capacity